2016
DOI: 10.3109/01443615.2015.1133574
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of frozen section for borderline ovarian tumours

Abstract: Borderline ovarian tumours (BOTs) are characterised histologically by a low degree of cellular proliferation and nuclear atypia in the absence of infiltrative growth or stromal invasion. Surgical treatment has been a crucial component of BOT therapy. Surgical decisions are established intraoperatively via the frozen section. We evaluated the accuracy of frozen section diagnosis. The rate of correct diagnosis, underdiagnosis and overdiagnosis of BOTs with frozen sections was 78%, 17% and 5%, respectively. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Frozen section could not yield an accurate diagnosis in borderline ovarian tumors (Bozdag et al, 2016). Increased numbers of frozen sections could not increase the accuracy of the reading (Ayhan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Frozen section could not yield an accurate diagnosis in borderline ovarian tumors (Bozdag et al, 2016). Increased numbers of frozen sections could not increase the accuracy of the reading (Ayhan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that frozen section should be used cautiously in borderline tumors, particularly in older patients and in mucinous tumors [18]. Other studies suggest that frozen section is insufficient for accurate diagnosis of BOTs due to risk of underdiagnosis [19,20]. The present study highlights the continued challenges of borderline tumors diagnosis at FS with 13 discrepant cases, 3 of whom, required additional surgery.…”
Section: Discussionmentioning
confidence: 64%
“…Unlike in many other tumors, no preoperative pathological diagnosis should be performed in early ovarian cancer. Oncologists depend mainly on pathological examination of the excised ovarian tumor (11) . Performing a complete surgical staging for every patient with a complex ovarian mass is a double-edged weapon.…”
Section: Discussionmentioning
confidence: 99%